Microeconomic principles and problems : a pluralist introduction - Schneider, Geoffrey Eugene (New York, NY : Routledge, 2024)
"Microeconomic Principles and Problems offers a comprehensive introduction to all major perspectives in modern microeconomics, including mainstream and heterodox approaches. By providing multiple views of markets and how they work, readers will be better able to understand and analyse the complex behaviours of consumers, firms, and government officials, as well as the likely impact of a variety of economic events and policies. Most principles textbooks cover only mainstream economics and neglect the rich contextual analysis of heterodox economists. Heterodox material is presented as complementary to mainstream economics: understanding both approaches yields the deepest level of understanding. The book covers standard models, and includes substantial coverage of existing economic realities, featuring case studies and descriptive data. The book includes some coverage of all major heterodox schools of thought. This second edition incorporates new and expanded material on international trade (including disintegration and Brexit), climate issues and perspectives including degrowth, inter-temporal exchanges and games, non-market exchanges, trends in job opportunities, the rising cost of education, the gig economy, social media as an industry, and updated examples and cases. The book's suite of digital resources has also been revised to ensure examples and activities are relevant to each part of the book. Written in an engaging style focused on real-world examples, this groundbreaking book brings economics to life. It offers the most contemporary and complete package for any pluralist microeconomics class"--Provided by publisher.
Includes bibliographical references and index.
Keywords: Macroeconomics